Rancang Bangun Sistem Keamanan Rumah Terintegrasi Telegram Menggunakan Mikrokontroler ATMega328 - Habib Nurfaizal (Faktor Exacta, 2023)
Crime can happen anywhere and anytime. The security system is important. Much will be done to make conditions secure, one of them is home security. Home is a place to stay that must be guarded. Everyone will anxious if leaving home when empty. Usually home security uses CCTV cameras. Many theft cases show that using a CCTV camera is less effective. It is not enough to use a camera to monitor the state of the house, then we need a system that can give real-time notifications to home-owners via Telegram. Telegram is a cloud-based and free instant messaging service. Telegram also provides a bot system. When creating a new bot on a telegram, can monitor the state of the house by receiving telegram messages through sensors that have been identified. This system is made using ATMega 328 Arduino board as a microcontroller and NodeMcu ESP8266 as a wifi that can give notifications if there is movement, fire, and gas leakage in the house.